Qualitative review of published studies in the field of Environmental Psychology in Costa Rica - von Breymann Miranda, Helga (2026)
This article presents the main findings of a qualitative review on Costa Rican scientific production in environmental psychology. The central objective was to identify the topics addressed and the contributing disciplines by analyzing research published in national journals between 2010 and 2022. The results reveal an incipient yet growing field, with a predominance of studies on the perception of insecurity, risk, and public space, contrasting with less attention to the natural environment, climate change, and mental health. Furthermore, a higher number of publications appears in architecture and engineering journals compared to psychology journals, suggesting a notable interest in design and construction regarding the space-individual relationship and associated psychological processes. These findings delineate promising areas for future research and reinforce lines of global impact such as sustainability.